A hemostatic powder capable of rapidly absorbing liquid and rapidly gelling
By mixing aldehyde-modified polysaccharides and polyamino polymer powders and adding NHS ester-polyacrylic acid-gelatin powder, the problem of hemostasis difficulties in existing hemostatic materials in cases of wounds that cannot be pressed and massive bleeding scenarios is solved, achieving hemostatic effects of rapid liquid absorption, gelation and strong adhesion.
Patent Information
- Application Number
- CN202311759122.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-20
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2043-12-20
AI Technical Summary
Existing hemostatic materials are not effective in situations where pressure cannot be applied to wounds or in cases of severe bleeding. Traditional gauze application poses a risk of secondary injury, while existing hemostatic powders are slow to stop bleeding and inconvenient to use.
Aldehyde-modified polysaccharide powder and polyamino polymer modified powder were mixed at a mass ratio of 1:(1-5). The aldehyde-modified polysaccharide powder was prepared by sodium periodate reaction, dialysis and freeze-drying, and the polyamino polymer powder was prepared by pH adjustment and freeze-drying. After mixing, a hemostatic powder that rapidly absorbs liquid and gels was formed. NHS ester-polyacrylic acid-gelatin powder was added to improve adhesion and water absorption.
It achieves rapid fluid absorption and rapid gelation, making it suitable for wounds that cannot be pressed and scenarios with massive bleeding. It significantly improves hemostasis without affecting intrinsic and extrinsic coagulation pathways and is easy to use.
Smart Images

Figure CN117731824B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of medical materials technology, specifically relating to a hemostatic powder that can rapidly absorb liquid and rapidly gel. Background Technology
[0002] Rapid and effective hemostasis can save lives and reduce injuries and fatalities from traumatic accidents. Traditional hemostasis methods have many limitations. For example, while gauze pressure can stop bleeding quickly, it is ineffective for areas where pressure cannot be applied, such as internal organs. Furthermore, changing gauze can easily cause secondary damage to the wound and even lead to infection. Moreover, traditional hemostatic gauze and sponges cannot be torn and inserted into the body through a channel less than 1 cm in diameter to reach the bleeding point, limiting their application scenarios. Hemostatic powder, with its natural fluid properties, offers advantages such as rapid hemostasis, easy absorption and decomposition, non-obstruction of the surgical field, and high clinical safety, making it more suitable for applications involving new catheters and laparoscopic surgeries. Especially in cases of diffuse bleeding requiring rapid hemostasis, hemostatic powder can replace traditional hemostatic sponges and gauze currently available on the market.
[0003] Patent CN 109432488 A discloses a method for preparing a chitosan / gelatin composite hemostatic powder, characterized by obtaining the chitosan / gelatin composite hemostatic powder through an emulsification reaction. This material possesses certain water absorption properties, which can accelerate wound hemostasis; however, its average hemostasis time is 240 seconds, and the coagulation-promoting effect is not yet ideal, thus exhibiting certain limitations.
[0004] Patent CN 106620825 A discloses a two-component rapid hemostatic gel and its application. The gel is composed of a mixture of two liquids (aldehyde-modified natural polysaccharide solution and amino-modified polymer solution). This material exhibits rapid gelation time and adhesion, but requires application to the wound using a double-bore syringe, making it inconvenient to use. Furthermore, its application in scenarios with slightly larger bleeding volumes may affect the concentration of the two components, thus impacting their gelation time and adhesion.
[0005] Hemostatic powders are convenient to use and provide rapid hemostasis, making them widely applicable in clinical and emergency settings. However, they often exhibit issues such as low wet adhesion and are unsuitable for fatal, incompressible bleeding sites. Therefore, there is an urgent need to develop hemostatic powders with superior performance. Summary of the Invention
[0006] To address the problems in the prior art, this invention provides a rapidly absorbable and gelatinizable hemostatic powder and its preparation method to solve the aforementioned issues. It should be noted that all concentration percentages mentioned in this invention are percentages of solute mass to solvent volume, expressed in g / mL.
[0007] This invention provides a hemostatic powder that can rapidly absorb liquid and rapidly gel, wherein the hemostatic powder is obtained by mixing and grinding aldehyde-modified polysaccharide powder and polyamino polymer modified powder in a mass ratio of 1:(1-5); preferably, the mass ratio of aldehyde-modified polysaccharide powder and polyamino polymer modified powder is 1:2.
[0008] The aldehyde-modified polysaccharide powder is obtained through the following preparation process: A mixed aqueous solution is obtained by adding 10-30% sodium periodate aqueous solution to a 2-5% polysaccharide aqueous solution, wherein the volume ratio of the dextran aqueous solution to the sodium periodate aqueous solution is (2-10):1; the mixed aqueous solution is reacted in the dark at 20-60℃ and 500-1500rpm for 2-10 hours, followed by the addition of ethylene glycol for 1-4 hours to obtain a reaction solution, wherein the molar ratio of ethylene glycol to sodium periodate is (0.5-2):1; the reaction solution is dialyzed in a dialysis bag with a molecular weight cutoff of 1000 Daltons for 12-72 hours, preferably 48 hours, to obtain an aldehyde-modified polysaccharide aqueous solution; the pH of the aldehyde-modified dextran aqueous solution is adjusted to 3-5, followed by freeze-drying and grinding to obtain aldehyde-modified dextran powder; the polysaccharide in the polysaccharide aqueous solution is selected from one or more of dextran, sodium alginate, carboxymethyl cellulose, and chitosan.
[0009] The modified polyamino polymer powder is prepared by adjusting the pH of a 1-20% polyamino polymer aqueous solution containing 0.5-20% excipients to 7-9, followed by freeze drying and grinding; the polyamino polymer is selected from polylysine, α-polylysine, and ε-polylysine; the excipients are one or more of mannitol, sucrose, and trehalose.
[0010] Preferably, the polysaccharide aqueous solution is a dextran aqueous solution, and the concentration of the dextran aqueous solution is 4%, the concentration of the sodium periodate aqueous solution is 26%, and the raw material preparation volume ratio of the dextran aqueous solution to the sodium periodate aqueous solution is 5:1;
[0011] Preferably, the mixed aqueous solution is reacted at 37°C and 500 rpm in the dark for 6 hours, followed by the addition of ethylene glycol and a reaction for 2 hours to obtain the reaction solution. The molar ratio of ethylene glycol to sodium periodate is 1:1.16.
[0012] Preferably, the first pH adjuster used to adjust the pH of the aldehyde-modified dextran aqueous solution is any one of 0.1-1% acetic acid aqueous solution, 0.1-1% orthophosphoric acid aqueous solution, and 0.1-1% hydrochloric acid aqueous solution; more preferably, the first pH adjuster is 0.1-1% hydrochloric acid aqueous solution; furthermore, the preferred pH value of the aldehyde-modified dextran aqueous solution after pH adjustment is 4.28.
[0013] Preferably, the polyamino polymer is ε-polylysine, the excipient is mannitol, and the content of mannitol is 0.5-2%; and more preferably, the concentration of the ε-polylysine aqueous solution is 10% and the content of mannitol as the excipient is 1%.
[0014] Preferably, the second pH adjuster for the polyamine polymer solution is a 1-20% sodium hydroxide aqueous solution, more preferably a 10% sodium hydroxide aqueous solution; further, the preferred pH value of the polyamine polymer solution after adjustment is 8.15.
[0015] The hemostatic powder provided by this invention has the advantages of rapid water absorption, high water absorption rate, and fast gelation speed. When the hemostatic powder is applied to the bleeding site, it first rapidly absorbs water from the blood, concentrating blood cells and clotting factors, and promoting blood coagulation. Simultaneously, after adhering to the tissue, the hydrated aldehyde-modified dextran and ε-polylysine in the hemostatic powder fully gel, transforming the powder into a tough hydrogel that seals the bleeding site, slows bleeding, and prevents continuous blood flow from the bleeding opening, achieving rapid hemostasis.
[0016] To further improve the adhesion and absorbency of the hemostatic powder, enabling it to meet the hemostatic needs in scenarios with significant bleeding, as a preferred embodiment of the present invention, the hemostatic powder further includes NHS ester-polyacrylic acid-gelatin powder; that is, the hemostatic powder is uniformly mixed from NHS ester-polyacrylic acid-gelatin powder, aldehyde-modified polysaccharide powder, and polyamino polymer powder, and the mass ratio of the NHS ester-polyacrylic acid-gelatin powder, aldehyde-modified polysaccharide powder, and polyamino polymer powder is (0-1):(0.1-1):1;
[0017] The NHS ester-polyacrylic acid-gelatin powder NHS-PAA is prepared by sequentially adding 5-15% gelatin aqueous solution, 5-15% ammonium persulfate aqueous solution and acrylic acid mixed solution to the oil phase, stirring at 20-80℃ and 500-1500rpm for 1-5h, then centrifuging, washing and freeze-drying.
[0018] Wherein, the 5-15% gelatin aqueous solution, the 5-15% ammonium persulfate aqueous solution, and the acrylic mixed solution are all aqueous phases, and the volume ratio of the aqueous phase to the oil phase is 1:(1-10); the acrylic mixed solution is an aqueous solution containing 1-10% acrylic acid, 5-20% sodium acrylate, and 1-10% acrylate-N-succinimide ester; the oil phase is an organic solution containing 0.2-1% emulsifier;
[0019] The gelatin is one or more of type A and type B gelatin, and the gel strength of the gelatin is in the range of 50-300g Bloom; preferably 125-250g Bloom.
[0020] The emulsifier is one or more of Span-60, Span-65, Span-80, Tween-60, Tween-65, and Tween-80, and the organic solution is one or more of liquid paraffin, petroleum ether, corn oil, soybean oil, and peanut oil.
[0021] Preferably, the washing solution used for centrifugal washing is one or more of dimethyl sulfoxide, tetrahydrofuran, dichloromethane, ethyl acetate, and organic solvents, and more preferably dichloromethane;
[0022] Preferably, the mass ratio of the NHS ester-polyacrylic acid-gelatin powder, the aldehyde-modified polysaccharide powder, and the polyamino polymer powder is 0.7:0.4:1.
[0023] In a preferred embodiment of the present invention, the hemostatic powder further includes NHS ester-polyacrylic acid-gelatin powder. When applied to a wet tissue surface, the hemostatic powder first rapidly absorbs fluid from the wound interface and then quickly expands to absorb surface fluid. Without additional pressure, the carboxyl groups in the NHS-PAA of the hemostatic powder form temporary cross-links with the tissue surface through intermolecular bonds. Subsequently, covalent cross-linking occurs between the NHS ester groups in the NHS-PAA and the primary amine groups on the tissue, providing strong and stable adhesion to the hemostatic powder gel. After the hemostatic powder adheres to the tissue, the hydrated aldehyde-modified dextran and ε-polylysine in it fully gel, transforming the hemostatic powder into a tough hydrogel that seals the bleeding site, slows bleeding, and prevents continuous blood flow from the bleeding opening, achieving rapid hemostasis.
[0024] Compared with the prior art, the beneficial technical effects of the present invention are as follows:
[0025] Compared with the hemostatic powder disclosed in patent CN 109432488 A, the hemostatic powder provided by the present invention has a significantly shorter gelation time and has the effects of rapid liquid absorption and rapid gelation.
[0026] Compared with the hemostatic agent disclosed in patent CN 106620825 A, the hemostatic powder provided by this invention is convenient to use as a powdered hemostatic material, and can meet basic water absorption requirements and maintain a relatively fast gelation rate. The preparation method of the hemostatic powder described in this invention is simple, has low production cost, and is suitable for large-scale production.
[0027] The present invention provides a preferred hemostatic powder, which further includes NHS ester-polyacrylic acid-gelatin powder components. It can be used for bleeding from regular or irregular wounds. In addition to its general hemostasis, it is more importantly suitable for hemostasis of large amounts of bleeding or wounds that cannot be pressed, thus changing the current situation where it is difficult to stop bleeding in wounds that cannot be pressed. Moreover, this hemostatic powder does not have a negative impact on intrinsic and extrinsic coagulation pathways. At the same time, it can promote the coagulation process through effective adhesion, accelerate the formation of blood clots, and achieve rapid hemostasis. Attached Figure Description
[0028] Figure 1 This is a photograph of the rapid water absorption and expansion process in Experiment Example 5;
[0029] Figure 2 Photographs of the gelation process of Experiment 33 on the surface of wet sausage casings;
[0030] Figure 3 Photographs of the adhesion test process on the surface of wet casing in Experiment 33;
[0031] Figure 4 Photographs of the gelation process on the surface of wet casings in Experiment 34;
[0032] Figure 5 This is a photograph of the adhesion test process on the surface of wet sausage casing in Experiment 34. Detailed Implementation
[0033] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and specific experimental examples. It should be understood that the following experimental examples are merely illustrative and explanatory of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are covered within the scope of protection intended by the present invention. Furthermore, unless otherwise specified, all raw materials, reagents, instruments, and equipment used in the present invention can be obtained commercially or prepared using existing methods. The following are some of the sources of raw materials involved in the comparative and experimental examples:
[0034] The dextran was purchased from Maclean's, with a molecular weight of 70,000;
[0035] Sodium periodate was purchased from Innochem, with a purity of 99.5%.
[0036] ε-polylysine was purchased from Maclean P980822, with a molecular weight of 1000-5000;
[0037] Type B gelatin was purchased from Exploration, AR; CAS number 9000-70-8, gel strength (6.67% solution): ≥180g Bloom;
[0038] Twain 80 was purchased from Energie AR grade;
[0039] The corn oil was purchased from Tansun, RG grade.
[0040] Compare with Example 1
[0041] Comparative Example 1 provides a hydrogel composed of a 20% aldehyde-modified dextran solution and a 10% ε-polylysine solution, and seven experiments were conducted. Experiments 1-7 were identical except for the volume ratio of the 20% aldehyde-modified dextran solution and the 10% ε-polylysine solution. The preparation of the 20% aldehyde-modified dextran solution and the 10% ε-polylysine solution in Experiments 1-7 were carried out according to the following preparation methods:
[0042] The preparation process of 20% aldehyde-modified dextran solution, i.e. 20% OD solution, includes: (1) preparing 4% dextran aqueous solution; (2) preparing 26% sodium periodate aqueous solution; (3) adding 50 ml of sodium periodate aqueous solution to 250 ml of dextran aqueous solution, reacting it in the dark at 37℃ and 500 rpm for 6 h, then adding 4 ml of ethylene glycol and reacting for 2 h to obtain the reaction solution, placing the reaction solution in a dialysis bag with a molecular weight cutoff of 1000 Daltons and dialyzing for 48 h, after which aldehyde-modified polysaccharide aqueous solution is obtained; (4) freeze-drying it to obtain aldehyde-modified dextran; (5) using 1% hydrochloric acid aqueous solution to adjust the pH of aldehyde-modified dextran aqueous solution to 4.28, i.e., obtaining 20% aldehyde-modified dextran solution, i.e. 20% OD solution.
[0043] The preparation process of 10% ε-polylysine solution, i.e. 10% PL solution, includes: preparing a 10% ε-polylysine aqueous solution, using a 10% sodium hydroxide aqueous solution, and adjusting the pH of the ε-polylysine aqueous solution to 8.15, thus obtaining the 10% ε-polylysine solution, i.e. 10% PL solution.
[0044] 1) Gel formation behavior test: According to Table 1, add 20% OD solution and 10% PL solution to a clean centrifuge tube in sequence, start timing, vortex, stop timing after gelation, and the measured time is the gelation time.
[0045] 2) Water Absorption Test: The water absorption of the gel prepared in step 1) of the gelation behavior test was performed: the initial weight W0 of the gel was weighed, 15 ml of purified water was added, and the gel was incubated in a 37°C water bath shaker for 2 hours. After incubation, excess water was removed, and the gel was weighed again (W1). The formula for calculating the water absorption rate is as follows:
[0046] Water absorption rate (%) = [(W1-W0) / W0]*100
[0047] The test results are shown in Table 1:
[0048] Table 1
[0049]
[0050] Experimental results show that OD and PL are easy to crosslink in solution to form hydrogels, but the gelation time varies under different ratios and they exhibit different gel states.
[0051] The gelation process of OD and PL: When OD and PL solutions are mixed together, the initially very low-viscosity solution gradually becomes viscous, loses its fluidity, and eventually forms a gel. Based on this, the time it takes for the mixed solution of OD and PL to completely form a gel is defined as the gelation time.
[0052] The time required for complete gelation varied depending on the ratio of OD and PL, as shown in Table 1. Experiments 3-5 had the shortest gelation time, approximately 20 seconds. Comparing the gel states of different experiments, experiments 1-2 and 7 exhibited a softer, more moist state; experiments 4-6 showed a more brittle and fragile state; and experiment 3 produced the most intact gel with the best mechanical properties. Considering the gelation time, gel state, and water absorption rate, experiment 3 demonstrated the best performance among experiments 1-7.
[0053] Although Control Example 1 has some water absorption, the amount of water absorbed is relatively small. Even if the best formula in Experiment 3 of Control Example 1 is used to prepare the hemostatic agent, its water absorption is insufficient to meet the requirements for rapid hemostasis. Furthermore, since Experiments 1 to 7 in Control Example 1 are all two-component solutions, when they are applied to hemostasis, the liquid environment at the bleeding site will affect the cross-linking reaction of the two-component solution, which is equivalent to diluting the actual concentration of OD and PL solutions. This results in poor gel performance and water absorption, thereby affecting the hemostatic effect. Therefore, it is not suitable for situations with large bleeding volumes.
[0054] Experimental Example 1
[0055] Experimental Example 1 is based on Control Example 1, but the two-component solution in Control Example 1 is optimized into a two-component powder to verify whether the two-component solution in Control Example 1 can be directly powdered and mixed for use as a hemostatic powder.
[0056] Experiment 1 specifically provides a mixed powder composed of aldehyde-modified dextran powder and ε-polylysine powder. Ten experiments were set up. In Experiments 8-17, all conditions were the same except for the mass ratio of aldehyde-modified dextran powder and ε-polylysine powder. The preparation processes of the aldehyde-modified dextran powder and the ε-polylysine powder in Experiments 8-17 were as follows:
[0057] Preparation of aldehyde-modified dextran powder (OD powder): (1) Prepare a 4% dextran aqueous solution; (2) Prepare a 26% sodium periodate aqueous solution; (3) Add 50 ml of sodium periodate aqueous solution to 250 ml of dextran aqueous solution, react it in the dark at 37℃ and 500 rpm for 6 h, then add 4 ml of ethylene glycol and react for 2 h to obtain the reaction solution. Place the reaction solution in a dialysis bag with a molecular weight cutoff of 1000 Daltons and dialyze it for 48 h. After dialysis, an aldehyde-modified polysaccharide aqueous solution is obtained; (4) Use 1% hydrochloric acid aqueous solution to adjust the pH of the aldehyde-modified dextran aqueous solution to 4.28, freeze dry it, and grind it to obtain aldehyde-modified dextran powder, i.e., OD powder.
[0058] Preparation of ε-polylysine powder (PL): (1) Prepare a 10% ε-polylysine aqueous solution; (2) Use a 10% sodium hydroxide aqueous solution to adjust the pH of the ε-polylysine aqueous solution to 8.15, freeze-dry it, and grind it to obtain ε-polylysine powder, i.e., PL powder.
[0059] According to Table 2, weigh each component and grind and mix them evenly to obtain a two-component powder.
[0060] 1) Gelation behavior test: According to Table 2, weigh different components into clean vials, add 1 ml of purified water and start timing, vortex, and stop timing after gelation. The measured time is the gelation time. After gelation, add another 2 ml of purified water to determine the gelation ability of the sample. The formation of a stable hydrogel in water without dispersed particles indicates the in-situ gelation ability of the sample.
[0061] 2) Water Absorption Test: According to Table 2, weigh different components into clean centrifuge tubes, add 1 ml of purified water to form a gel, then add 40 ml of purified water to the centrifuge tubes and incubate in a 37℃ water bath shaker for 2 hours. After incubation, remove excess water and weigh. The formula for calculating the water absorption rate is as follows, and the experimental results are shown in Table 2:
[0062] Water absorption rate (%) = [(wet weight - dry weight) / dry weight] * 100
[0063] Table 2
[0064] Experimental Example 1 PL status OD:PL (mass ratio) Gel formation time (s) 2h water absorption Experiment 8 dry powder 4:1 12.32 487% Experiment 9 dry powder 3:1 10.20 582% Experiment 10 dry powder 2:1 8.32 468% Experiment 11 dry powder 1:1 7.84 443% Experiment 12 dry powder 1:2 8.45 257% Experiment 13 dry powder 1:3 10.57 175% Experiment 14 dry powder 1:4 12.25 78% Experiment 15 Adhesive and clumped together 4:1 18.61 Unable to sample Experiment 16 Adhesive and clumped together 2:1 17.87 Unable to sample Experiment 17 Adhesive and clumped together 1:1 15.26 100%
[0065] The experimental results of Example 1 show that the two-component powder can quickly hydrate and form a gel after contact with water. Compared with Control Example 1, the gel formed in Example 1 has greater water absorption and is more suitable for use in humid environments.
[0066] The gelation process of OD and PL powders: When uniformly mixed OD and PL powders come into contact with water, the OD and PL powders first rapidly redissolve. Simultaneously, the redissolved portion undergoes a rapid chemical reaction to form a gel, until the entire mixture is gelled. The gelation speed of OD and PL powders is crucially determined by the redissolution rate of the powders. Factors such as the powder state of OD and PL, and the reaction ratio, will affect properties such as gelation time, gel state, and water absorption rate.
[0067] The problem with Experiment 1 is that PL powder is extremely susceptible to moisture. It will clump together in a short time after it is in its original powder state. In Experiments 15 to 17, the PL powder clumped together after being left for 10 minutes. This resulted in a longer gelation time, a worse gel state and water absorption after mixing with OD powder, and a deterioration in overall performance, as shown in Table 2. Therefore, the PL powder needs to be optimized.
[0068] Experiment Example 2
[0069] Experimental Example 2 is based on Experimental Example 1. The PL powder in Experimental Example 1 was optimized by using mannitol as a protective agent for PL to verify that the PLM powder prepared by modifying it with mannitol as a protective agent in Experimental Example 2 can maintain a dry powder state without sticking together, and that it does not affect the gelation and water absorption properties when mixed with OD powder as a hemostatic powder.
[0070] Experiment 2 specifically provides a mixed powder composed of aldehyde-modified dextran powder (OD powder) and ε-polylysine modified powder (PLM powder). Four experiments were set up. In Experiments 18 to 21, except for the different mass ratios of aldehyde-modified dextran powder and ε-polylysine modified powder, all other conditions were the same. The preparation of aldehyde-modified dextran powder in Experiments 18 to 21 was the same as that in Experiment 1. The preparation of ε-polylysine modified powder was carried out according to the following configuration method:
[0071] Preparation of ε-polylysine modified powder, i.e. PLM powder: (1) Prepare a 10% ε-polylysine aqueous solution containing 1% mannitol; (2) Use a 10% sodium hydroxide aqueous solution to adjust the pH of the ε-polylysine aqueous solution to 8.15, freeze-dry it, and grind it to obtain ε-polylysine modified powder, i.e. PLM powder.
[0072] According to Table 3, each component was weighed and ground until homogeneous to obtain Experimental Example 2. The gelation behavior test and water absorption rate test of Experimental Example 2 were the same as those of Experimental Example 1, and the results are shown in Table 3.
[0073] Table 3
[0074]
[0075] The experimental results of Example 2 show that using mannitol as a protective agent for PL can produce PLM that maintains its dry powder state. Furthermore, the introduction of an appropriate amount of mannitol does not affect the resolution and rapid cross-linking reaction of OD and PLM, and the gel maintains high water absorption. The optimal ratio is OD:PLM = 1:2, yielding a gel with rapid gelation, intact gel state, and optimal water absorption.
[0076] Experimental Example 3
[0077] Experiment 3, based on Experiment 2, investigated the effect of mannitol addition on powder gelation to verify that the amount of mannitol added has a significant effect on the state of PL powder and affects the gelation time and water absorption of the final mixed powder.
[0078] Experiment 3 specifically provided a mixed powder composed of aldehyde-modified dextran powder and ε-polylysine modified powder with different mannitol contents. Two experiments were set up. Experiments 22 and 23 were identical except for the mannitol content. The preparation of the aldehyde-modified dextran powder in experiments 22 and 23 was the same as in Experiment 1. The preparation of the ε-polylysine modified powder was carried out according to the following method:
[0079] Preparation of ε-polylysine powder (PLM) with different mannitol contents: (1) Prepare 10% ε-polylysine aqueous solutions containing 0.1% and 10% mannitol respectively; (2) Use 10% sodium hydroxide aqueous solution to adjust the pH of the ε-polylysine aqueous solution to 8.15, freeze dry it, grind it, and obtain ε-polylysine modified powder, i.e., PLM powder.
[0080] According to Table 4, each component was weighed and ground until homogeneous to obtain Experimental Example 3. The gelation behavior test and water absorption rate test of Experimental Example 3 were the same as those of Experimental Example 1.
[0081] Table 4
[0082]
[0083] Compared to Experiment 2, and especially Experiment 19, the results of Experiment 3 show that when the amount of mannitol added is too small, it cannot protect PL. When the amount of mannitol added is too large, it will affect the gel state and water absorption of OD and PLM. When the amount of mannitol added is appropriate, it is possible to maintain the high water absorption of the gel without affecting the crosslinking reaction.
[0084] Experiment Example 4
[0085] Based on Experiment 2, Experiment 4 compared the differences between sucrose and mannitol as protective agents for PL to verify that mannitol is a better protective agent.
[0086] Experiment 4 specifically provided a mixed powder composed of aldehyde-modified dextran powder and ε-polylysine modified powder. Three experiments were set up. In experiments 24 to 26, the conditions were the same except for the mass ratio of aldehyde-modified dextran powder to ε-polylysine modified powder. In experiments 22 and 23, the preparation of aldehyde-modified dextran powder was the same as that in Experiment 1. The preparation of ε-polylysine modified powder was carried out according to the following method:
[0087] Preparation of ε-polylysine powder (PLS): (1) Prepare a 10% ε-polylysine aqueous solution containing 1% sucrose; (2) Use a 10% sodium hydroxide aqueous solution to adjust the pH of the ε-polylysine aqueous solution to 8.15, freeze-dry it, and grind it to obtain ε-polylysine powder, i.e., PLS powder.
[0088] According to Table 5, each component was weighed and ground until homogeneous to obtain Experimental Example 4. The gelation behavior test and water absorption rate test of Experimental Example 4 were the same as those of Experimental Example 1.
[0089] Table 5
[0090]
[0091] Experimental results show that using sucrose as a protective agent for PL yields dry PLS powder, and the addition of an appropriate amount of sucrose does not affect the cross-linking reaction between OD and PLS, while maintaining high water absorption of the gel. However, at the same ratio, using mannitol as a protective agent for PL achieves better water absorption of the gel.
[0092] The results of experiments 1-4 show that OD and PL can rapidly crosslink to form a hydrogel in powder form. The introduction of excipients such as mannitol and sucrose does not affect the rapid dissolution and crosslinking reaction of each component. Considering gelation time, gel state, mechanical properties and water absorption, Experiment 19 in Experiment 2 shows the best overall effect when mannitol is used as a protective agent for PL and OD:PLM = 1:2.
[0093] Experimental Example 5
[0094] Experimental Example 5 consists of a single component, NHS ester-polyacrylic acid-gelatin powder (NHS-PAA).
[0095] Preparation of NHS ester-polyacrylic acid-gelatin powder (NHS-PAA): (1) Prepare a 10% aqueous solution of type B gelatin as solution A; (2) Prepare a 10% aqueous solution of ammonium persulfate as solution B; (3) Prepare an aqueous solution containing 5% acrylic acid, 15% sodium acrylate and 2% N-succinimide acrylate as solution C; (4) Prepare corn oil containing 0.5% Tween 80 as the oil phase; (5) Add 10 ml of solution A, 7.5 ml of solution B and 5 ml of solution C (i.e., the aqueous phase) to 200 ml of the oil phase in sequence, stir at 60℃ and 1000 rpm for 3 h, centrifuge and wash with dichloromethane, freeze dry to obtain NHS ester-polyacrylic acid-gelatin powder (NHS-PAA).
[0096] Water absorption test: Weigh 60mg NHS-PAA powder into a 10ml vial, add 2ml of purified water to determine the water absorption capacity of the sample.
[0097] like Figure 1 As shown in the figures, Figure a shows NHS-PAA powder, and Figure b shows the powder swelling after adding 2ml of water to a vial. It can be seen that 2ml of water is quickly absorbed by the NHS-PAA powder, which rapidly absorbs water and swells into a gel powder, indicating that it has a high water absorption rate and strong water absorption capacity. 60mg of dry powder can absorb at least 30 times its own weight in liquid. Figure c shows that, based on Figure b, 3ml of water is added to the vial. As shown in Figure c, the NHS-PAA dry powder has already absorbed 2ml of liquid, and an additional 3ml of water is added. The gel powder continues to absorb water until it is saturated. However, because it cannot self-gel, the gel powder remains fluid when there is excess liquid.
[0098] The role of NHS-PAA powder in hemostatic powder: When hemostatic powder is applied to the surface of wet tissue, 1) NHS-PAA can quickly absorb the fluid at the wound interface, concentrate blood cells, clotting factors, etc., and promote blood coagulation; 2) NHS-PAA expands rapidly and absorbs the surface fluid, making the wet tissue surface dry; 3) The carboxyl groups in NHS-PAA form temporary cross-links with the tissue surface through intermolecular bonds, and then covalent cross-links occur between the NHS ester groups in NHS-PAA and the primary amine groups on the tissue, providing strong and stable adhesion for the hemostatic powder gel.
[0099] Therefore, based on the experimental results of Control Example 1 and Experimental Examples 1-5, further optimizations were made, such as using NHS-PAA dry powder in combination with the two-component solution in Control Example 1, or using NHS-PAA dry powder in combination with the two-component powder in Experimental Example 2. These methods can further improve the absorption and hemostasis effects on the original basis.
[0100] Experimental Example 6
[0101] Experiment 6 consisted of NHS-PAA powder, 20% OD solution, and 10% PL solution. Three experiments were set up. In Experiments 27 to 29, the preparation of NHS-PAA powder was the same as in Experiment 5, and the preparation of 20% OD solution and 10% PL solution was the same as in Control Example 1.
[0102] The experimental procedures for Experiments 27 to 29 are as follows: In a clean centrifuge tube, NHS-PAA powder was first added, followed by different volumes of water. Specifically, the water volumes added in Experiments 27 to 29 were 0, 0.2 ml, and 1 ml, respectively. Then, 200 μL of 20% OD solution and 200 μL of 10% PL were added. After gelation, the results were observed and are shown in Table 6.
[0103] Table 6
[0104]
[0105] The problem with Comparative Example 1 is that excessive liquid volume in the environment significantly affects the gelation of OD and PL solutions, even preventing gelation altogether. When using a two-component solution, different proportions of NHS-PAA powder can be added depending on the liquid environment to pre-form a drier interface, thus not affecting the gelation reaction of the OD and PL solutions and achieving hemostasis. However, even with the use of NHS-PAA powder to pre-form a drier interface, allowing the OD and PL solutions to gel, the gel has lower water absorption, and its water absorption effect is not as good as in Experiments 1-5.
[0106] Experimental Example 7
[0107] Experiment 7 consisted of NHS-PAA powder, OD powder, and PLM powder. Three experiments were set up: in Experiments 30-32, the preparation of NHS-PAA powder was the same as in Experiment 5, the preparation of OD powder was the same as in Experiment 1, and the preparation of PLM powder was the same as in Experiment 2. According to Table 7, NHS-PAA powder, OD powder, and PLM powder were weighed, ground, and mixed evenly to obtain Experiments 30-32. The gelation behavior test and water absorption rate test of Experiment 7 were the same as in Experiment 1.
[0108] Table 7
[0109] Experimental Example 7 NHS-PAA:OD:PLM (mass ratio) gelation time 2h water absorption rate Experiment 30 0.3:0.4:1 12.43 1905% Experiment 31 0.7:0.4:1 13.42 2880% Experiment 32 1:0.4:1 13.76 2462%
[0110] When applied to the wet tissue interface in Experiment 7, all three dry powders in Experiment 7 rapidly absorbed water. NHS-PAA absorbed a large amount of water rapidly, drying the tissue interface. OD and PLM quickly re-dissolved and simultaneously underwent a cross-linking reaction to form a gel, thereby achieving a sealing effect. Compared to Experiments 1-6, Experiment 7 showed a significantly improved liquid absorption capacity, making it particularly suitable for scenarios with large bleeding volumes. The additional NHS-PAA powder further enhanced the water absorption rate. When NHS-PAA:OD:PLM = 0.7:0.4:1, the gel formed by the hydration of the dry powder exhibited the best integrity and the highest water absorption rate.
[0111] To evaluate the adhesion properties of the hemostatic powder provided by this invention, the following comparative experiments were conducted:
[0112] Experiment 33: Cut collagen sausage casings with a diameter of 40mm into 60×15mm pieces. 2 The flakes are stored in deionized water at 2°C until use. Wipe off the water from the surface of the casing, as shown. Figure 2 As shown in Figure a, 400 μL of the same 20% OD solution as Control Example 1 and 200 μL of 10% PL solution were injected onto the surface of the sausage casing, and then... Figure 2 As shown in Figure b, the solution gels on the surface of the casing. Figure 3 As shown in Figure a, when the gel is impacted at any point by natural water flow, the gel is partially broken after being washed by the water flow, as shown in Figure a. Figure 3 As shown in Figure b, the gel and casing already adhered to the casing were treated as a whole and soaked in excess saline for 24 hours. For easier observation, the gel and casing were removed and dried at room temperature. The integrity and adhesiveness of the gel were then observed. Figure 3 As shown in Figure c, the gel was completely broken down after being rinsed and soaked in water.
[0113] Experiment 34: Cut collagen sausage casings with a diameter of 40mm into 60×15mm pieces. 2 The flakes were stored in deionized water at 2°C until use. 0.07g of NHS-PAA (same as in Example 5), 0.04g of OD powder (same as in Example 1), and 0.08g of PLM powder (same as in Example 2) were weighed and mixed thoroughly to form a hemostatic powder. The water on the surface of the casing was wiped off. Figure 4 The diagram illustrates the gelation process of hemostatic powder on the surface of sausage casings. As shown in Figure a, the dry powder is sprinkled onto the casing surface. As shown in Figure b, 1 ml of water is added to allow the powder to form a gel. As shown in Figure c, the gel remains intact. Figure 5 As shown in Figure a, the gel is impacted at any point by natural water flow, such as... Figure 5 As shown in Figure b, the gel already adhered to the casing and the casing were treated as a whole and soaked in excess saline for 24 hours. For easier observation, as shown... Figure 5As shown in Figure c, the gel that has adhered to the casing and the casing were removed and dried at room temperature. The integrity and adhesion of the gel were observed. It can be found that after being rinsed and soaked in water, the gel in Experiment 34 did not move or fall off and remained tightly adhered to the casing.
Claims
1. A hemostatic powder that rapidly absorbs liquid and can quickly gel, characterized in that, The hemostatic powder is obtained by mixing and grinding aldehyde-modified polysaccharide powder and polyamino polymer modified powder in a mass ratio of 1:(1~5); The aldehyde-modified polysaccharide powder is obtained through the following preparation process: A 2-5% polysaccharide aqueous solution is mixed with 10-30% sodium periodate aqueous solution to obtain a mixed aqueous solution, wherein the polysaccharide aqueous solution is a dextran aqueous solution; the volume ratio of the dextran aqueous solution to the sodium periodate aqueous solution is (2-10):1; the mixed aqueous solution is reacted in the dark at 20-60℃ and 500-1500rpm for 2-10 hours, followed by the addition of ethylene glycol for 1-4 hours to obtain a reaction solution, wherein the molar ratio of ethylene glycol to sodium periodate is (0.5-2):1; the reaction solution is dialyzed in a dialysis bag with a molecular weight cutoff of 1000 Daltons for 12-72 hours, and after dialysis, an aldehyde-modified dextran aqueous solution is obtained; the pH of the aldehyde-modified dextran aqueous solution is adjusted to 3-5, and then it is freeze-dried and ground to obtain aldehyde-modified dextran powder; The modified polyamino polymer powder is prepared by adjusting the pH of a 1-20% polyamino polymer aqueous solution containing 0.5-20% excipients to 7-9, followed by freeze drying and grinding; the polyamino polymer is selected from polylysine; the excipients are one or more of mannitol, sucrose, and trehalose.
2. The hemostatic powder that rapidly absorbs liquid and can rapidly gel as described in claim 1, characterized in that, The mass ratio of the aldehyde-modified polysaccharide powder to the polyamino polymer modified powder is 1:
2.
3. The hemostatic powder that rapidly absorbs liquid and can rapidly gel as described in claim 1, characterized in that, The concentration of the dextran aqueous solution is 4%, the concentration of the sodium periodate aqueous solution is 26%, and the raw material preparation volume ratio of the dextran aqueous solution to the sodium periodate aqueous solution is 5:
1.
4. The hemostatic powder that rapidly absorbs liquid and can rapidly gel as described in claim 1, characterized in that, The mixed aqueous solution was placed at 37°C and 500 rpm in the dark for 6 hours and then reacted with ethylene glycol for 2 hours to obtain the reaction solution. The molar ratio of ethylene glycol to sodium periodate in the raw material preparation was 1:1.
16.
5. The hemostatic powder that rapidly absorbs liquid and can rapidly gel as described in claim 1, characterized in that, The pH of the aldehyde-modified dextran aqueous solution was adjusted to 4.
28.
6. The hemostatic powder that rapidly absorbs liquid and can rapidly gel as described in claim 1, characterized in that, The polylysine is α-polylysine or ε-polylysine, and the excipient is mannitol, with a mannitol content of 0.5-2%.
7. The hemostatic powder that rapidly absorbs liquid and can rapidly gel as described in claim 6, characterized in that, The concentration of the ε-polylysine aqueous solution is 10%, and the excipient is mannitol, with a mannitol content of 1%.
8. The hemostatic powder that rapidly absorbs liquid and can rapidly gel as described in claim 1, characterized in that, The pH value of the polyamino polymer aqueous solution after adjustment is 8.
15.
9. A hemostatic powder that rapidly absorbs liquid and can rapidly gel, characterized in that, The hemostatic powder is based on the hemostatic powder with rapid liquid absorption and rapid gelation as described in claim 1, with the addition of NHS ester-polyacrylic acid-gelatin powder, and the mass ratio of the NHS ester-polyacrylic acid-gelatin powder, aldehyde-modified polysaccharide powder and polyamino polymer modified powder is (0~1):(0.1~1):
1. The NHS ester-polyacrylic acid-gelatin powder (NHS-PAA) is prepared by sequentially adding 5-15% gelatin aqueous solution, 5-15% ammonium persulfate aqueous solution, and acrylic acid mixed solution to an oil phase, stirring at 20-80℃ and 500-1500 rpm for 1-5 h, followed by centrifugation, washing, and freeze-drying. The 5-15% gelatin aqueous solution, 5-15% ammonium persulfate aqueous solution, and acrylic acid mixed solution are all aqueous phases, with a volume ratio of aqueous phase to oil phase of 1:(1-10). The acrylic acid mixed solution is an aqueous solution containing 1-10% acrylic acid, 5-20% sodium acrylate, and 1-10% acrylate-N-succinimide ester. The oil phase is an organic solution containing 0.2-1% emulsifier. The gelatin is one or more of type A and type B gelatin, and the gel strength of the gelatin ranges from 50 to 300 g Bloom. The emulsifier is one or more of Span-60, Span-65, Span-80, Tween-60, Tween-65, and Tween-80, and the organic solution is one or more of liquid paraffin, petroleum ether, corn oil, soybean oil, and peanut oil.
10. The hemostatic powder that rapidly absorbs liquid and can rapidly gel as described in claim 9, characterized in that, The mass ratio of the NHS ester-polyacrylic acid-gelatin powder, aldehyde-modified polysaccharide powder, and polyamino polymer modified powder is 0.7:0.4:1.
Citation Information
Patent Citations
Preparation method of chitosan / gelatin composite hemostatic microspheres
CN109432488A
Bi-component quick haemostatic gel and application thereof
CN106620825A
Tissue adhesive for antibody solution
CN115052638A
